Management of common cattail (Typha latifolia) with florpyrauxifen-benzyl in rice fields - Deniz Inci; Michelle M. Leinfelder-Miles; Kassim Al-Khatib (Weed Technology)
Common cattail is a perennial weed that naturally occurs in wet or saturated soils, such as in marshes, lakes, ponds, irrigation and drainage canals, and streams, throughout North America. Recently, common cattail has become an important problem for the drill-seeded rice systems in the Sacramento–San Joaquin River Delta of northern California. This research was conducted in 2022 and 2023 at three sites near Stockton, CA, to evaluate the efficacy of florpyrauxifen-benzyl, a newly registered auxin-mimic herbicide, to control common cattail in drill-seeded rice. Florpyrauxifen-benzyl was applied alone at 40 g ai ha–1 and 80 g ha–1 on 0- to 1-m-tall and 1- to 2-m-tall common cattail and in a sequential application of florpyrauxifen-benzyl at 40 g ha–1 followed by 40 g ha–1 between 14-d intervals on 0- to 1-m-tall and 1- to 2-m-tall common cattail. Triclopyr, another auxin-mimic rice herbicide widely used in California, was applied alone at 420 g ae ha–1 on 0- to 1-m-tall common cattail for comparison. Triclopyr was also applied in combination with florpyrauxifen-benzyl at 40 g ha–1 at the 0- to 1-m growth stage. The injury symptoms on common cattail started within 3 d after treatment (DAT) for the florpyrauxifen-benzyl + triclopyr mixture treatment and within 7 DAT for all other florpyrauxifen-benzyl applied treatments. All florpyrauxifen-benzyl treatments controlled 100% of common cattail at 28 DAT regardless of application rate and timing. Common cattail height and dry biomass at 28 DAT were lower for all treatments compared to the nontreated control. While the common cattail control was excellent for all florpyrauxifen-benzyl applications, rice injury was minimal. This research indicates that common cattail up to 2 m tall can be effectively and rapidly controlled in rice fields with florpyrauxifen-benzyl at 40 g ha–1.